Antipruritic properties of topical Channa striatus extract on stratum corneum disruption-itch mice model - Fauzi, Irfan; Farouk, Ahmad Akira Omar; Perimal, Enoch Kumar (Neurotak Publishing, 2022)
Itch is an unpleasant sensation that provokes a strong desire to scratch. In some cases, antihistamines are ineffective in treating chronic itch and produce side effects. Channa striatus fish extract, which can alleviate pain, is also used in this experiment to alleviate the itch. This experiment aims to determine the possible antipruritic effect of topical Channa striatus extract (CSE) on stratum corneum disruption (SCD)-itch mice model. Experiments were divided into 6 groups of male ICR mice which were positive, negative, vehicles, 3% CSE, 7% CSE, and 10% CSE groups. Rostral back of mice was induced with chemicals acetone, diethyl ether (1:1) and water (AcetoneEthylWatermethod) daily for five consecutive days. All groups were treated with specific selective treatments. The scratching behaviour of the mice was observed by videotape. The skin moisture and oiliness scoring was measured daily using a skin analyzer. The skin was isolated for RNA extraction and measured for tumour necrosis factor-alpha (TNF- α) gene expression level using real-time RT PCR. All treatment groups of Channa striatus extract cream had shown a significant reduction in scratching time, increase in skin moisture and skin oiliness. The TNF- α gene expression level had inconsistent results and needed a more extensive sample. The Channa striatus extract cream may be able to alleviate itch compared to the control parameters.